IMPROVING LECTURERS’ PAEDAGOGIC COMPETENCE THROUGH THE IMPLEMENTATION OF LESSON STUDY IN FACULTY OF TEACHER TRAINING AND EDUCATION OF PAKUAN UNIVERSITY, INDONESIA - Eri Sarimanah (JETL (Journal of Education, Teaching and Learning), 2016)
This research is aimed at improving the lecturers of Faculty of Teacher Training and Education of Pakuan University paedagogic competence through the implementation of lesson study which covers learning management competence including developing chapter design and lesson design, media making, teaching and learning, evaluation, post evaluation follow-up and learning supervision. This research involves four study program. The method used in this research is qualitative descriptive. The data are collected through documentation, observation, interview and questionnaire. The data are analyzed descriptively to investigate the improvement of the lecturers’ paedagogic competence in teaching through the implementation of lesson study. Lesson study has been implemented for two years in Indonesian and Literature Education Study Program, English Education Study Program, Biology Education Study Program, and Primary Education Study Program. The findings show that there is an improvement of the lecturers paedagogic competence in developing chapter design and lesson design, developing material and designing media for learning (plan stage); running the lesson (do stage); and observing the lesson as well as evaluating and reflecting it (see stage). Besides, it is found the lecturers develop learning innovation to create students’ active learning. The colleagality among the lecturers is also develop well through the implementation of lesson study. The questionnaire result also shows that the implementation of lesson study can make the student become autonomous learners.